1978
DOI: 10.1148/128.2.315
|View full text |Cite
|
Sign up to set email alerts
|

The Barium Enema: A Reassessment Looking Toward Perfection

Abstract: In a crossover study of more than 300 double contrast colon examinations, including 2,200 radiographs, many common and some uncommon views were taken and compared. An optimal series of "routine" films and the order in which they should be taken are presented. This will produce a complete colon examination in the most efficient way. Some technical considerations are presented which proved necessary to produce a superb examination. This new routine represents a reduction in the number of films advocated by Welin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…So, too, might colonic distension associated with constipation. However, as a counter to this theory, there are no reports of spinall nerve root discomfort during enema procedures (Peterson and Miller, 1978;Bartram, 1986) when such a posteriomedially situated colon might exert pressure on ventral rami. Moreover, there are few reports of involvement of ventral rami by colonic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…So, too, might colonic distension associated with constipation. However, as a counter to this theory, there are no reports of spinall nerve root discomfort during enema procedures (Peterson and Miller, 1978;Bartram, 1986) when such a posteriomedially situated colon might exert pressure on ventral rami. Moreover, there are few reports of involvement of ventral rami by colonic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The DCBE technique was usually similar to that described by Peterson and Miller [11]. Intravenous Buscopan (Boehringer Ingelheim (NZ) Ltd., Auckland, New Zealand) at 20 mg was usually administered.…”
Section: Methodsmentioning
confidence: 99%
“…Early proponents of the DCBE recommended that a large number of overhead projections be obtained routinely during DCBE [7,8]. Recently, studies have analyzed the efficacy of the different views and have indicated those with the highest yield of diagnostic information [9,10].…”
Section: Introductionmentioning
confidence: 99%